Resim Sanatı Üzerine Okumalar 3 - Tosmur, Necla; Parsıl, Ümit; Sayın Yücel, Hüda; Özdemir, Çiğdem; Usal, Yelda; Şener, Nilgün; Aydın, Nursel; Tunçoğlu, Eda; Güngör, Tuğba; Yıldırım, Dila (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-